Diagnostic value of serum carbohydrate antigen 19-9 in pancreatic cancer: a systematic review and meta-analysis. Issue 9 (27th July 2022) - Zhao, Boqiang; Zhao, Boyue; Chen, Fangyao
Abstract : Carbohydrate antigen 19-9 (CA19-9) is the most widely used serum biomarker for detecting pancreatic cancer (PC). Since early diagnosis is important for improving PC prognosis, a comprehensive understanding of the diagnostic performance of CA19-9 is critical. This study focused on comprehensive evaluation of the efficacy of CA19-9 in PC diagnosis. Literature research was based on the seven databases. Studies released from January 2002 to January 2022 focused on the efficacy of CA19-9 in the detection of PC were included. Summarized sensitivity, specificity, and sROC/accuracy of discrimination (AUC) were estimated. Potential publication bias was measured with Funnel plot and Egger's test. Meta-regression was performed to detect possible causes of heterogeneity. Subgroup analysis was used to assess the diagnostic efficacy of CA19-9 under different conditions. The study is registered on PROSPERO (CRD42021253861). Seventy-nine studies containing 20 991 participants who met the criteria were included. The pooled sensitivity, specificity, and AUC of CA19-9 in diagnose PC were 72% (95% CI, 71–73%), 86% (95% CI, 85–86%), and 0.8474 (95% CI, 0.8272–0.8676). Subgroup analysis suggested that the diagnostic efficiency of CA19-9 in studies with healthy controls was the highest, followed by intraductal papillary mucinous neoplasm, in pancreatitis and diabetes were consistent with the overall result. Our analysis showed that serum CA19-9 had high and stable diagnostic efficacy for PC (not affected by diabetes). Subgroup analysis showed that serum CA19-9 yielded highest effectiveness in the diagnosis of pancreatic precancerous lesions, which indicated an irreplaceable clinical value in the early detection and warning value for PC.